Synthesis and structure of high‐purity BaCe0.25Mn0.75O3: an improved material for thermochemical water splitting. Issue 6 (15th November 2022) - Bell, Robert T.; Strange, Nicholas A.; Plattenberger, Dan A.; Shulda, Sarah; Park, James Eujin; Ambrosini, Andrea; Heinselman, Karen N.; Sugar, Joshua D.; Parilla, Philip A.; Coker, Eric N.; McDaniel, Anthony; Ginley, David S.
Abstract : Synthesis of the perovskite‐like layered 12R phase of BaCe0.25 Mn0.75 O3 (12R‐BCM) at higher yields (> 97 wt%) than previously reported. The influence of sintering temperature and redox cycling on the composition and weight fraction of secondary phases is investigated. The anisotropy between thermal expansion along the c ‐axis and within the ab plane is examined with synchrotron‐based diffraction measurements. Abstract : Solar thermochemical hydrogen production (STCH) via redox‐active metal oxides is an approach for direct solar‐driven hydrogen generation typically using a high‐temperature redox cycle involving refractory oxides and steam. Typical cycles involve high‐temperature reduction of oxides to form oxygen vacancies, followed by lower temperature reaction between oxygen vacancies and steam where the oxide is re‐oxidized and the steam is reduced to hydrogen. Only a few materials have demonstrated reversible cycling under the typically harsh STCH conditions ( e.g. 1500°C reduction, 900°C re‐oxidation) and critical questions remain on the true reversibility of non‐stoichiometric multi‐cation oxide systems, significantly hampered by the lack of single‐phase samples for these material systems. To date, most STCH processes have relied on CeO2 as a benchmark active material, but more recently, the 12R phase of BaCe0.25 Mn0.75 O3 (BCM) has demonstrated greater hydrogen‐generation potential at lower peak temperatures. However, previous reports of 12R‐BCM have included large fractions, > 10 wt%, of secondary phases, which complicate analysis of the stability and performance. A comprehensive understanding of the redox mechanism and reversibility of the process in BCM can only be achieved with nearly single‐phase samples which, to date, have been difficult to produce. Here two approaches to BCM synthesis are reported: solid state and sol–gel‐based routes. It is demonstrated that both routes can be tuned to produce the 12R structure with > 97 wt% yield when annealed ≥1450°C. Herein synchrotron‐based diffraction measurements of rhombohedral 12R‐BCM enabled characterization of the anisotropy between thermal expansion along the c ‐axis and within the ab plane. The impact of high‐temperature redox cycling on the stability and phase fraction of the 12R‐BCM polytype was also investigated. These results offer two viable routes for synthesis of high‐purity 12R‐BCM critically needed for evaluating the efficacy of BCM as a STCH material and validate its ability to split water at lower temperatures over extended numbers of redox cycles.